Complete chloroplast genome sequences of Wonwhang (Pyrus pyrifolia) and its phylogenetic analysis. Issue 1 (1st January 2017) - Chung, Ho Yong; Lee, Tae-Ho; Kim, Yoon-Kyeong; Kim, Jung Sun
Abstract: The complete chloroplast genome of Wonwhang (BioSample SAMN05196235), Pyrus pyrifolia, was assembled and analyzed by de novo assembly using whole-genome sequencing data. The accession NC_015996 was used as a reference sequence in this study. The total chloroplast genome size of the Wonwhang was 159, 922 bp in length, including a pair of inverted repeat regions (IRs) of 26, 392 bp that are separated by a large single-copy region of 72, 023 bp and a small single-copy region of 19, 235 bp. A total of 132 genes, including 93 protein-coding genes, 31 tRNA genes and eight rRNA genes, were predicted from the chloroplast genomes. Among them, 18 genes occur in IRs, containing nine protein-coding genes, five tRNA genes and four rRNA genes. The GC content of Wonwhang chloroplast genome is 36.6%. The phylogenetic analysis with nine Rosids species and three other species revealed that Wonwhang was clustered with Malus genus.